State activity of the khan of Minor zhuzh (horde) Abulkhair and the Ottoman Sultan Suleiman (Journal of actual problems of jurisprudence, 2019)
This article describes the state activity of the Khan of Minor zhuzh (horde) Abulkhair and the Ottoman SultanSuleiman. Sets out the political situation during the era of the officials and military, diplomatic relations withthe neighboring states as well as the scientific study comparing the political and military action.Keywords: military-diplomatic actions, military-political position, military qualities, diplomacy power,political choice.